2005
DOI: 10.1111/j.1467-9817.2005.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of computerised spelling training in children with language impairments: a comparison of modified and unmodified speech input

Abstract: This study evaluated a computerised program for training spelling in 8-to 13-yearolds with receptive language impairments. The training program involved children typing words corresponding to pictured items whose names were spoken. If the child made an error or requested help, the program gave phonological and orthographic cues to build up the word's spelling. Eleven children received this training with ordinary speech, and eleven had the same program but with speech modified to lengthen and amplify dynamic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
(26 reference statements)
0
15
0
1
Order By: Relevance
“…This was unexpected as decoding and spelling are closely associated (e.g., Christopher et al, 2012) and the failure could be due to several possibilities including the relatively high standardised scores for spelling at pre-test and the need for lengthy consolidation before decoding gains translate into spelling gains. In addition, improvements in decoding may not necessarily translate to spelling (Hughes et al, 2013) and even computer interventions that target spelling have not been successful (Bishop, Adams, Lehtonen & Rosen, 2005).…”
Section: Effectiveness Of a Computer-assisted Interventionmentioning
confidence: 99%
“…This was unexpected as decoding and spelling are closely associated (e.g., Christopher et al, 2012) and the failure could be due to several possibilities including the relatively high standardised scores for spelling at pre-test and the need for lengthy consolidation before decoding gains translate into spelling gains. In addition, improvements in decoding may not necessarily translate to spelling (Hughes et al, 2013) and even computer interventions that target spelling have not been successful (Bishop, Adams, Lehtonen & Rosen, 2005).…”
Section: Effectiveness Of a Computer-assisted Interventionmentioning
confidence: 99%
“…This game also lasted 15 minutes, also used modified or unmodified speech to give feedback about grapheme-phoneme correspondences, and was typically completed in the same session as the grammar game. Results from the Spelling Game are presented elsewhere (Bishop et al 2005b).…”
Section: Grammar Training Programmentioning
confidence: 99%
“…Van Daal and Reitsma (2000) reported that with these programmes, spelling progress was enhanced for kindergarten children and reading‐disabled students. Other researchers have found success with teaching reading to reading‐disabled students more difficult to achieve (eg, see Bishop, Adams, Lehtonen & Rosen, 2005; Wood, 2005).…”
Section: Facilitating the Skills Of Learningmentioning
confidence: 99%